IMPLEMENTASI SISTEM ACTIVITY BASED COSTING TERHADAP PERHITUNGAN HARGA POKOK PRODUK (Studi Kasus pada The Redwood City Plan of Crimson Components Company) - Septi - Wifasari (Universitas Pamulang, 2017)
AbstractWith the Activity Based Costing (ABC) system, it will improve the existing deficiencies in the conventional system in terms of as a basis for managers in decision making. Many companies can improve planning, product costing, operational controls and management controls by using activity analysis to develop a detailed picture of the activity providing the basis for Activity Based Costing. Activity Based Costing is used to improve the accuracy of cost analysis by improving the way cost tracking to cost objects. Activity Based Costing is used for different cost objects of individual products, interrelated product groups and individual customers. This system is useful when company ops is complex with many product types and manufacturing processes. Keywords: Activity Based Costing, conventional system, cost object, product cost, cost of product